Evaluation and monitoring of the satisfaction of meat and meat products consumers - Corina, Constanta Rușeț (Agroprint Timisoara, 2018)
The managers have to be focused on clients and satisfy their needs, so that the products meet their expectations. The evaluation and monitoring the consumers satisfaction is very important because it is a managerial instrument which offers the possibility to understand and satisfy the needs of the existing consumers. In this study we used the questionnaire as research method and after analyzing and processing the data we noticed the consumers preferences related to the meat and meat products consumption, the frequency of consumption and the places from where the consumers procure their meat and meat products.